2022
DOI: 10.31661/jbpe.v0i0.1912-1036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forward Head Posture on Dynamic Balance Based on the Biodex Balance System

Abstract: Forward Head Posture (FHP) results in spine malalignment, muscle imbalance and cervical proprioception sensory input impairment. Subjective description of FHP is interpreted differently by clinicians and therefore the FHP is classified as slight, moderate and sever. This study aimed to evaluate balance disorder in individuals with severe forward head posture (FHP). Twenty individuals with severe FHP and 20 controls were enrolled. Dynamic postural stability was assessed in all participants using the Biodex Bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Studies have found that there is a significant association between neck pain and forward head posture, with higher risks of having neck pain in female and older populations [3]. It is generally believed that this abnormal posture is associated with the development and persistence of spine pain and various biomechanically driven disorders [4][5][6][7][8][9][10]. For example, researchers have identified that FHP alters the cervical range of motion (ROM) [4], contributes to an abnormal balance [5,6], and alters respiratory efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have found that there is a significant association between neck pain and forward head posture, with higher risks of having neck pain in female and older populations [3]. It is generally believed that this abnormal posture is associated with the development and persistence of spine pain and various biomechanically driven disorders [4][5][6][7][8][9][10]. For example, researchers have identified that FHP alters the cervical range of motion (ROM) [4], contributes to an abnormal balance [5,6], and alters respiratory efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that this abnormal posture is associated with the development and persistence of spine pain and various biomechanically driven disorders [4][5][6][7][8][9][10]. For example, researchers have identified that FHP alters the cervical range of motion (ROM) [4], contributes to an abnormal balance [5,6], and alters respiratory efficiency [7]. It has been readily seen in the past decade that there has been a surge in interest in forward head posture in surgical [8,9] and conservative rehabilitation settings alike [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding an individual's jumping and gait mechanics is crucial, particularly when considering the spinal factors that may affect these parameters. One such factor is head posture, which is proposed to play a significant role in the overall relationship between movement patterns and spinal alignment [8][9][10][11][12][13]. It is plausible that alterations in gait and jump performance are associated with abnormal head posture; this hypothesis stems from the understanding that deviations in head posture can detrimentally affect both postural control and proprioception [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%